Effects of the Smoking Cessation Intervention Combining Toe Sheath Acupressure with Motivational Interviewing - Mongkhonsiri, Pitsini; Srathong, Pussadee; Chaiwongsa, Kedkanya; Rasiri, Somtakul; Wanchai, Ausanee; Ngudgratoke, Sungworn; Jitaram, Parinya; Inthongparn, Orachorn; Jiamamornrat, Rujira; Kitsomporn, Jureerat (Journal of The Royal Thai Army Nurses, 2023)
Tobacco use is a major public health problem worldwide. This study examined the effects of the invented toe sheath acupressure (TSA) combined with motivational interviewing (MI) as a treatment for smoking cessation. One hundred and sixteen smokers were divided into 4 groups: control group, MI group, TSA group, and MI plus TSA group. Data were collected at baseline and 1, 3, 6, and 9 months after interventions. Data were analyzed by using repeated measures MANCOVA. Results showed that smokers (68.97%) reported that there was a high level of the unpleasant smell of cigarettes after using the invented TSA which made them reduce smoking cravings. The treatments could significantly reduce smoking (F (3,925.354) = 4.444, p = .006, Eta Squared (η2) = .116). The control group showed significantly higher cigarettes smoked per day than those in the MI group and the MI plus TSA group (∆ = 6.485, p = .015; ∆ = 6.125 , p = .026, respectively). In conclusion, using only MI may be sufficient to facilitate smoking cessation as the results were not different when compared to the MI plus TSA treatment. However, the TSA applied reflexology could be an alternative means to initiate quitting smoking. Also, MI should be used to affirm cognitive modification for smokers.